EFFECT OF ALMONDS AND ATENOLOL ON SERUM LUTEINIZING HORMONE LEVEL IN MALE BALB-C MICE - Rehman, Irum; khan, Shakir; ashraf, ifra; naveed, ayesha; masood, farheen (Pakistan Journal of Physiology, 2018)
Background: Along with other advantageous effects nuts are good for fertility and can improve derangements in different fertility parameters. With increasing incidence of hypertension leading to an increase in consumption of antihypertensives it is inevitable to depart their side effects. This study was designed to see the effect of administration of Prunus amygdalus, atenolol and combination of atenolol and Prunus amygdalus on level of serum luteinizing hormone (LH) in male Balb-C mice. Methods: This experimental study was conducted from December 2013 to June 2014. One hundred and twenty mice fulfilling inclusion criteria were divided into 4 groups of 30 mice each. Group A served as control group, group B mice were given atenolol, group C mice were given extract of almonds and group D mice were given atenolol and almonds. After the completion of 3 months, blood sampling was done and serum LH was measured. Data was analyzed on SPSS-17, MeanÂ±SD was calculated for luteinizing hormone levels. One-way ANOVA was applied and pâ‰¤0.05 was considered significant. Results: The mean value of serum LH in group B (Atenolol treated) was found to be significantly elevated. In group C (Almonds) serum LH was decreased but not significantly. Mean serum LH level in group D (Atenolol+Almond) was raised as compared to control group, but not significantly. Conclusion: Administration of Prunus amygdalis does not affect serum LH but atenolol causes a rise in serum LH.